A influência das ações de responsabilidade social na legitimidade organizacional de uma empresa do setor elétrico - Erika Rubia de Souza (2011)
Legitimacy study is a relevant theme for Organizations studies, which has often been referred to by literature and widely discussed on an Organizational basis. In this context, this research was carried out aiming at analysing the impact of an electricity area company´s social responsibility actions on its reputation, as well as assessingthese actions influence on its free coorporative clients´ support behavior. The theoretical structure that guides the present work is based on instrumental and normative proposals that discuss the organization goals using a perspective approach either neoclassic or institutional. Considering methodoly, it was used a quali-quanti case study, in which primary and secondary data were analised. In the first part of quality study, publicity tools and sustainability reports produced by theresearched company were analised, with the objective of identifying howcoorporative responsibility issue has been worked on for the past 3 years. Besides, interviews with 4 Cemig executives from communication and sustainability areas were carried out. The information gathered in these investigations were analised using Content Analysis. The second step was to conduct interviews with eight huge free cooporative clients. Quantitative research was made by applying a questionnaireto the 280 free coorporative clients that have relationship with this company. Data were treated using SPSS Statistics 17.0.2 software, wich allowed Variance Analysis tests (ANOVA), Pearson´s Correlation Coefficient, Multinomial Logistic Regression and Determination Coefficient. The quali-quanti results indicate that the actions ofsocial responsibility applied by the company interfere more on its reputation rather than on the support behavior showed by the free cooporative clients. Most of these clients support their decisions on energy purchase on a logical cost reduce; seek for efficiency in the operations; short-term growth and profitability, a perspectivedescribed by neoclassic theory. The technical capacity showed by the energy provider appears as the most relevant element to justify the purchase decision of the free coorporative clients. Although social responsibility is not the major factor considered by clients in their choice for an energy provider, it appears as an important element to legitimate their strategic decisions. On a very realistic basis, it was clearly expressed by clients that they consider social responsibility actions moreas formal demands and/or image to the market, rather than moral or ethical coorporative commitment that companies should have. Thus, social responsible actions give the researched company Regulatory, Normative and Cognitive Legitimacy derived from a solid coorporative reputation.